Application of Social Competence (ASCAAL) to improve student learning creativity in the online learning system (SPADA) in the Covid-19 Pandemic Era - Siahaan, Mungkap Mangapul; Purba, Rudiarman; Sianturi, Tambos August (Journal of Education Technology, 2021)
Social competence ensures teaching objectives in the SPADA system that knows no boundaries of space and time for teachers and students. 54% of Indonesian teachers do not have sufficient competence to teach. It has an impact on the lack of learning objectives that are not achieved optimally. This study aims to investigate the innovation of two groups of students in learning English Syntactic Structure. With purposive sampling technique, ASCAAL was measured from the results of several methods in the form of a questionnaire, pretest and posttest given to 45 students. The group is the control class and the experimental class that study Syntactic Structure. The experimental class consisted of 25 students, and the control class consisted of 20 students. One group teaches with SPADA, and the other teaches with social media facilities such as Google Classroom and WhatsApp. The technique used to analyze the data is descriptive qualitative and quantitative analysis. The result of the research is that ASCAAL is proven to be positive in increasing students' creativity. ASCAAL also supports a positive learning management system. The features and menus on SPADA show a developing learning creativity system that increases student motivation and value.